The Global Expansion of UBER in ASIAN Markets - Bugador, Roderick Caballero (ExcelingTech, 2019)
This paper analyzes the global expansion of UBER in Asia. The perspective is based on the context of internationalization process of ICT companies, especially the ride-hailing developer firms. The expansion of Uber was aggressive using a standard business model in every market that they get into. They focused on scale economy rather than localization of their services. The case analysis suggests that UBER is unsuccessful in its global expansion due to a number of factors especially the host economy context and local competition. Eventually, the company retreated in Asia and refocused its efforts in their home market. The case shows that the global expansion of ride-hailing firms is not as easy as the born global perspective would predict, as there are still a lot of frictions in the global market.